AB1046 A Meta-Analysis of Mortality in Rheumatoid Arthritis. (10th June 2014) - Toledano, E.; Loza, E.; Carmona, L.; Ortiz, A.; Villaverde, V.; Martínez-Ruíz, J.A.; Lajas, C.; Castañeda, S.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic diseases with a great burden from disability and complications that ultimately lead to large losses of quality of life and cumbersome dependency. Data reporting mortality in RA vary widely. Objectives: To provide an accurate overview of the current risk of mortality in AR. Methods: Systematic review of published studies identified by sensitive electronic searches of MEDLINE, EMBASE and Cochrane Library until April 2013 were performed by trained researchers using free text and MeSH synonims of "mortality" and of "RA". Elegibility criteria were 1) study population with RA; (2) outcome of interest mortality, reported as an standardized mortality ratio (SMR); and (3) meta-analysis, systematic reviews, cohorts or longitudinal observational studies. Assessment of risk of bias relied on the New Castle-Ottawa scale for cohorts. Only moderate to high quality studies were included. Results: See Table 1 . A total of 17 studies with data from several million patients were included, between 47 and 65 years, 75% women and follow up from 3 to 40 years. General population was used as reference. The overall SMR was from 1.25 (95% CI 1.18–1.33) to 4.58 (4.33-4.83). By gender, from 0.87 (0.63-1.21) to 4.97 (4.53-5.59) in men and from 1.02 (0.78-1.33) to 5.05 (4.73-5.37) in women. By pathologies, the SMR were higher for infections than cardiovascular and cancer disease. Mortality declined in recent studies. Conclusions: Mortality is increased in RA, and it is supported by moderate to high quality cohort studies. The causes of death in our review actually match those of the general population, where cardiovascular events and cancer are the most frequent causes, but notably, infections and respiratory complications are actually the causes related to an excess mortality in RA. Acknowledgements: This systematic review is part of GECOAR Project promoted by the Madrid Society of Rheumatology in collaboration with Roche. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3325